Extortion strategies resist disciplining when higher competitiveness is rewarded with extra gain - Lutz Becks (Nature Portfolio, 2019)
In game theory, ‘extortionate’ tactics in two-player games are predicted to give way to ‘generous’ strategies. Here, the authors show in a human experimental sample that extortion can prevail as a strategy in games in which there is a specific reward for doing better than the other player.